USE OF EDUCATIONAL TECHNOLOGIES IN PREPARING FUTURE TEACHERS FOR INNOVATIVE ACTIVITY - Nurmakhanovna , Amirkhanova Diana (Journal of Higher Education and Academic Advancement, 2024)
The modern education system requires the formation of a creative person who can independently receive new information, evaluate it and draw appropriate conclusions